The Role of Brand Image in Mediating Social Media Marketing and Customer Relationship on the Decision to Choose a Private University - Setyowati, Trias; Widjayanti, Fefi Nurdiana; Kristiyana, Naning (Universitas Muhammadiyah Ponorogo, 2025)
This research aims to examine the impact of social media marketing and consumer relationships on the decision-making process regarding enrollment in private universities, as well as to assess their influence on the brand perception of these institutions. Additionally, it seeks to analyze how the perceived brand image affects the decision to enroll in a private university. The study targeted new students entering private universities in Jember Regency for the 2023/2024 academic year, using proportional random sampling methods for data collection via questionnaires. Statistical analysis and hypothesis testing were conducted using SEM-PLS methodology. Findings indicate that social media marketing significantly affects the decision to enroll in a private university, while consumer relationship factors do not. Moreover, both social media marketing and consumer relationships impact the brand image of private universities, which subsequently influences enrollment decisions. Indirect testing reveals that brand image serves as a mediating factor in the relationship between social media marketing, consumer relationships, and the decision to enroll in a private university.